In vitro negative effects of beach-cast invasive marine seaweed Rugulopteryx okamurae across life-stages of a native foundational species - Gálvez-Pastor, Emma; Sánchez de Pedro Crespo, Raquel; García-Sánchez, María Jesús; Flores-Moya, Antonio; Bañares-España, Elena (Elsevier, 2025)
The exotic invasive seaweed Rugulopteryx okamurae (Dictyotales, Ochrophyta) have posed a serious threat to coastal and marine habitats since its appearance in 2015 in the Strait of Gibraltar. This, together with multiple global change stressors, is leading to the disappearance of native foundational seaweeds. Here we explored the potential impacts that decomposing thalli of beach-cast R. okamurae (BCRo) might have on different life-stages of a native foundational seaweed (Ericaria selaginoides, Fucales, Ochrophyta). The in vitro effects of different biomass densities of BCRo and time exposure, in combination with three warming scenarios, were assessed across single- and few-celled stages and adult thalli of the native species. We hypothesized that R. okamurae might interfere in the survival and growth of E. selaginoides either by allelopathic interactions or water acidification, due to low intracellular pH of R. okamurae tissues. Sensitivity of E. selaginoides to the exposure of BCRo was stage- and thermal-dependent and decreased during early ontogenesis. Unfertilized oospheres (female gametes) exposed to BCRo experienced apoptotic-like cell death within less than 180 s, while embryo survival and germination dropped by 50 % and 36 %, respectively. Warming effects were not additive to that of BCRo, since higher growth reductions in 7-d old juveniles of E. selaginoides were detected at lower (20 °C) but not at higher temperatures (28 °C). Adults of E. selaginoides were the less sensitive stage but their growth was up to 7-times lower under BCRo addition. BCRo acidified natural sea water proportionally to the density and incubation time, reaching a pH of 7.2 after 24 h. However, that pH was not limiting for E. selaginoides juveniles and even enhanced their growth, suggesting an alternative chemical effect.
Keywords: Invasiones biológicas marinas; Cystoseira; Ecología marina; Feofíceas; Biological invasions; Cystoseira s.l. forests; Dictyotales; Early life stages; Marine ecology; Recruits